The Role of Patience in Coping Mental Problems: A Quranic Perspective - Shinta Nuriya Idatul Alfain; Achmad Khudori Soleh; Muhammad Rafi Yamani (Tribakti: Jurnal Pemikiran Keislaman, 2023)
Mental health issues have become a growing concern in today's fast-paced and challenging world. In the quest for effective coping strategies, researchers and professionals are increasingly turning to ancient wisdom and religious scriptures for insights. This article explores the role of patience, as emphasized in the Quran, in addressing mental problems and promoting emotional well-being. The study delves into the Quranic verses and teachings that emphasize patience as a virtue and its potential impact on mental health. Drawing from the rich Islamic tradition, the article examines the concept of "Sabr" (patience) and its multifaceted dimensions, including perseverance, endurance, and emotional resilience. Furthermore, it explores how these qualities can be cultivated and practiced in dealing with various mental health challenges. The method used in this research is a content analysis with data in the form of verses from the Qur’an, and some researches related to patience. The findings of this study contribute to the growing body of literature on the intersection of spirituality and mental health, showcasing how religious teachings can offer a unique and valuable perspective on coping with mental problems. Moreover, it underscores the significance of embracing patience as a holistic approach to foster emotional well-being and promote resilience in the face of life's challenges, as emphasized in the Quranic teachings. The results of this study are 1) the word patient in the Qur’an is described more than a hundred times which generally explains that patience means self-restraint, emotion, and surviving in difficult conditions; 2) mental problems that are often experienced by people are anxiety, stress, depression, post-traumatic stress disorder, and behavioral disorders; 3) patience can be one of the treatments for mental disorders through self-control, self-acceptance, and resilience. The article concludes with implications for future research and clinical practice in the realm of mental health, emphasizing the need for a more comprehensive and culturally sensitive approach to address mental health issues in diverse populations.